Al-Barnāmaj al-Lughawī al-Mukaththaf fī Ta‘līm al-Lughah al-‘Arabiyyah fī Jāmi‘at al-Markaz al-Islāmī ‘Abdullāh Ghānim ash-Shamā’il Ponorogo wa Manhaj Ta‘līmihi - suryadharma, yoke; Yasin, Agus (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2018)
The need of Muslims towards Arabic learning is urgently needed, because the Arabic language is not only Arabian. It is the language of Muslims around the world. Because of individual differences within the Muslim, such as age, educational background, purpose of studying Arabic, etc., the learning of Arabic requires a specific curriculum to their needs for the learning of the Arabic language itself. In this paper, the researcher attempts to describe an example of Arabic learning, conducted on a community of Islamic Center Abdullah Ghonim Asy-Syamail Ponorogo East Java from February to September 2017 and it also explains the implementation of a curriculum consisting of several elements, such as the subjects taught, the books used and also the learning method used. The most important point put forward in this paper is that the ability to make an Arabic learning curriculum according to the needs of the Ummah or learners of Arabic is a vital [skill] that must be possessed by every Arabic teacher, in addition to teaching skills and mastery of four language skills.